A Review on the interaction between Nanoparticles and Toxic metals in Soil: Meta-analysis of their effects on soil, plants and human health. Issue 4 (19th May 2023) - Djibril Sekou, Keita; Patel, Harshad
ABSTRACT: The utilities of nanoproducts are inescapable in modern times due to the need of many technological companies. Still, concerns remain about their toxicity and possible environmental, health, and safety risks. Based on a meta-analysis of engineered nanoparticles (ENPs) toxic effects in the soil, this article sheds light on the toxicity of nanoparticles, toxic metals (TMs), and their synergistic toxicity. Several scientific research investigations have been held on the risk of nanoparticles (NPs) in the environment, but their toxicity and reactions toward coexistent contaminants remain challenging. According to our research, nanoparticles' effects on TMs' bioavailability depend on soil characteristics. This review article assessed the bioaccumulation of NPs and TMs in soils and plants. Furthermore, biomagnification of those toxicants in the human body and organisms has been discussed. It has been remarked that soil parameters played a crucial role in the bioavailability of these toxicants. In addition to this research paper, many other articles confirmed that nanoparticles' coexistence with TMs could amplify metals' toxicity in soil. Antecedent studies have been included to provide a comprehensive overview of the review. This review aimed to provide a deep understanding of the various aspects of the NPs and TMs and highlighted the multiple aspects of the toxicants and their harmful effects.